Choline increases serum insulin in rat when injected intraperitoneally and augments basal and stimulated aceylcholine release from the rat minced pancreas in vitro - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2003)
Intraperitoneal injection of choline (30-90 mg.kg(-1) ) produced a dose-dependent increase in serum insulin, glucose and choline levels in rats. The increase in serum insulin induced by choline (90 mg.kg(-1) ) was blocked by pretreatment with the muscarinic acetylcholine receptor antagonists, atropine (2 mg.kg(-1) ), pirenzepine (2 mg.kg(-1) ) and 4-diphenylacetoxy-N -methylpiperidine (2 mg.kg(-1) ) or the ganglionic nicotinic receptor antagonist, hexamethonium (15 mg.kg(-1) ). The effect of choline on serum insulin and glucose was enhanced by oral glucose administration (3 g.kg(-1) ). Choline administration was associated with a significant (P < 0.001) increase in the acetylcholine content of pancreatic tissue. Choline (10-130 mum) increased basal and stimulated acetylcholine release but failed to evoke insulin release from the minced pancreas at considerably higher concentrations (0.1-10 mm). Hemicholium-3, a choline uptake inhibitor, attenuated the increase in acetylcholine release induced by choline augmentation. Choline (1-32 mm) inhibited [(3) H]quinuclidinyl benzilate binding to the muscarinic receptors in the pancreatic homogenates. These data show that choline, a precursor of the neurotransmitter acetylcholine, increases serum insulin by indirectly stimulating peripheral acetylcholine receptors through the enhancement of acetylcholine synthesis and release.
Keywords: precursor; acetylcholine; parasympathetic; muscarinic receptors; nicotinic receptor; MUSCARINIC RECEPTOR SUBTYPES; ISLET HORMONE-SECRETION; ACETYLCHOLINE-RELEASE; CONSCIOUS RATS; TYROSINE-HYDROXYLASE; GLUCAGON-SECRETION; BRAIN; CITICOLINE; STRIATUM; DISEASE